Bio-inspired optimization design and fluid–solid-thermal multi-field verification analysis of labyrinth seal. (August 2022) - Cao, Xiaojian; Li, Jialiang; Liu, Jianlin
Graphical abstract: Highlights: A new snail shell structure is used as the prototype of the optimal design. The multi-objectives are changed into one objective through the weight coefficient. The designed labyrinth seal has good load-bearing and heat insulation performance. Abstract: Labyrinth seals are widely used in turbomachinery devices to prevent the leakage of fluid medium in seal structures. Under high parametrical environments, the heat generated by frictional resistance of the turbulence between the stator and rotor walls not only increases the temperature of the fluid and the solid, but also reduces the operation efficiency of the device. Therefore, it is necessary to implement the fluid–solid-thermal multi-field analysis of labyrinth seals and propose a comprehensive optimization design of the load-bearing and heat insulation. In the present study, inspired by a bionic snail shell, a sandwich structure with load-bearing material on both upper and lower surfaces and the heat insulation material in the middle is obtained through the genetic algorithm optimization. Then, the luid-solid-thermal multi-field analysis of the labyrinth seal with the sandwich structure is carried out. It is verified that the layer arrangement and layer thickness ratio of the bionic structure ensured the optimal performance of load-bearing and heat insulation. After changing the layer arrangement or layer thickness ratio, the comprehensive performance of load-bearing and heat insulation is obviously weakened. The result shows that the bionic multilayer sandwich structure can be applied to the labyrinth seal to achieve optimal comprehensive performance of load-bearing and heat insulation.